Dietary management improves sleep quality in patients with metabolic syndrome: the mediating roles of metabolic, inflammatory, and oxidative stress changes - Cheng, Junxiang; Liu, Qia; Qiu, Zhouli; Pan, Mengyi; Song, Jie; Zhao, Yu; Dong, Niuniu; Li, Suping; Han, Shifan (Frontiers in Nutrition, 2025)
BackgroundSleep disorders frequently co-occur with metabolic syndrome (MetS), yet effective strategies targeting both conditions remain limited. Inflammation and oxidative stress represent shared mechanisms, suggesting dietary management as a promising dual-target intervention. This study aimed to evaluate whether structured dietary management could improve sleep quality and metabolic, inflammatory, and oxidative stress parameters in patients with MetS.MethodsWe conducted a single-arm prospective interventional study including 158 patients with MetS and sleep disorders [Pittsburgh Sleep Quality Index (PSQI) > 7] between August and October 2024. Participants received a structured dietary management program. Clinical characteristics, metabolic parameters, and inflammatory and oxidative stress biomarkers were assessed before and after intervention. Paired tests evaluated pre–post changes, and stepwise multivariate linear regression was performed to identify independent predictors of sleep quality.ResultsDietary intervention significantly improved liver enzymes, lipid profile (triglycerides, LDL-C, HDL-C), glucose metabolism (fasting glucose, fasting insulin, HOMA-IR), and uric acid levels (all P < 0.05). TNF-α and hsCRP were markedly reduced (P < 0.001), while IL-6 showed a non-significant trend (P = 0.075). Oxidative stress improved, with lower MDA and higher SOD levels (P < 0.05). Regression analysis identified smoking status and insulin resistance as independent predictors of PSQI scores, underscoring the interplay between lifestyle factors and metabolic dysfunction in sleep health.ConclusionStructured dietary management improves metabolic, inflammatory, and oxidative stress profiles while enhancing sleep quality in patients with MetS. The findings highlight dietary and lifestyle modifications as integral to comprehensive management strategies for MetS with sleep disturbances.